Biocomposite tepexil cement reinforced with fibers of Agave angustifolia Haw. as a light mortar - Olivera, Andy A.; Caballero Caballero, Magdaleno; Alavéz Ramírez, Rafael; Chiñas Castillo, fernando; Montes Bernabé, José Luis; Silva Rivera, María Eugenia (Revista Mexicana de Ciencias Agrícolas, 2018)
The agave bagasse is a residual material obtained in the mezcal process. The accumulation of this material is considered an environmental problem in the communities that produce this spirit drink in an artisanal way. This waste contains optimal fibers for use as reinforcement material, obtaining an added value and reducing environmental pollution. In the development of a new material, you need to know its mechanical properties. To know if the new material is feasible, one of the most important properties is the resistance to compression. For this work, the objective was to determine the compressive strength of a biocomposite cement/tepexil matrix material, reinforced with agave bagasse fibers. To obtain the material, the fibers were washed with water with a pressure washer, dried in the open for 7 hours and ground in a knife mill to 1 mm in length. Subsequently, they were treated with an aqueous solution of 10% calcium hydroxide, for 34 h. Five different formulations were made with different proportions of fiber/tepexil. The compressive strength was measured on a Geotest universal machine at 7, 14 and 28 days. It was observed that in the increase of the proportion of fibers there is a decrease in the compressive strength and density of the biocomposite material. The optimum fiber ratio was 1:0:1 (Portland cement:tepexil:fiber), with a compressive strength of 6.19 MPa and a density of 1 366.73 kg/m3 at 28 days.